Perkembangan pemikiran ekonomi dan munculnya pandangan strukturalis - Edy Suandi Hamid (Economic Journal of Emerging Markets, 2001)
In the social sciences, economics is considered as the most progressive and dynamic science. Economics has a complete analysis tool, which combines both qualitative and quantitative approaches. In its process, the dynamics of economics is indicated by the emerge of new view with different approaches.